Rooting of semihardwood cuttings of olive: indolbutyric acid, calcium and Azospirillum brasilense - Rosa, Danimar Dalla; Villa, Fabíola; Silva, Daniel Fernandes da; Corbari, Fábio (Comunicata Scientiae, 2018)
Nowadays the semihardwood cuttings of olive is the most used method to produce seedlings of this specie; however, it is necessary to improve the efficiency of this method to enable the intensive exploitation of this fruit crop and reduce the seedling production costs. Thus, two experiments were conducted concurrently in sand bed, under a canvased shelter of the State University of Western Paraná (Brazil) to evaluate the number and average length of roots per cuttings, the percentage of rooted cuttings, cuttings with callus and dead cuttings. In the first experiment cuttings of olive cultivars Arbequina, Maria da Fé and clone 2 were treated with IBA (3.0 g L-1) associated with calcium concentration at 0.0; 0.25; 0.50 and 1.0 mmol L-1, implanted in a completely randomized design in a split plot design, with four replications containing ten cutting each, under intermittent mist. For this experiment the Arbequina cultivar presented the highest average number of roots per cutting and the highest percentage of rooted cuttings, but Maria da Fé cultivar promoted the highest average of cuttings with callus. In the second experiment Clone 2 cuttings were submitted to calcium (0.5 mmol L-1) and IBA (3.0 g L-1), and substrate inoculation with Azospirillum brasilense bacterium, implanted in a completely randomized design containing three replications of ten cuttings each. In this experiment, the highest percentage of rooted cuttings was obtained for IBA (3.0 g L-1) + A. brasilense.